Effect of Blended Lightweight and Normal Weight Aggregates on The Shear Capacity of Concrete Beams - Khalil, Khalid Hesham (2024)
A Master of Science thesis in Civil Engineering by Khalid Hesham Khalil entitled, “Effect of Blended Lightweight and Normal Weight Aggregates on The Shear Capacity of Concrete Beams”, submitted in November 2024. Thesis advisor is Dr. Farid Abed and thesis co-advisor is Dr. Sherif Yehia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).